Building-related resource use in Chinese eastern cities – Qingdao building stock as a case study - Zhu, Panyu; Mumm, Olaf; Zeringue, Ryan; Endres, Elisabeth; Miriam Carlow, Vanessa (Applied energy, 2022)
•Evaluation method for life-cycle resource use and carbon emission in buildings and neighbourhoods was proposed and demonstrated.•A matrix of building lifecycle carbon intensity was established, which could be used as a reference in design practice to simplify the process of estimation on large scales such as neighbourhood or city and still remain flexible to design changes.•The influence of urban density on carbon emissions was indicated by the comparison among 3 test areas.•The potential of achieving carbon neutral neighbourhoods by using sustainable strategies, such as material recycling and renewable energy application, was examined and proved to be possible. With China's ongoing urbanisation, large cities in the south eastern coastal areas entered a phase of rapid development and face many challenges, such as the need for housing alongside the depletion of resources. Continuously updated energy saving standards have been improving thermal condition of building envelopes throughout the last decades. However, less is known regarding the building life-cycle recourse use and carbon emission. Existing estimation methods are difficult to be used as a tool in design practice due to their complexity. In this study, focusing on the city of Qingdao as a case study, life-cycle resource use and carbon emission were investigated on the basis of typified buildings. A matrix of building carbon intensity was established, which can be used as a benchmark in design practice. It simplifies the process of estimation especially on large scale such as neighbourhood or city, and still remain the sensibility to design changes. As an application example, three neighbourhoods in Qingdao, differing in building and population densities, were comparatively analysed to determine the impact of urban density on carbon emission and to assess the possibility of achieving carbon neutrality; also by investigating the possibility of achieving this target through recycling and renewable energy. The findings could support the practice of sustainable urban planning in the future.